Pemeliharaan Sumberdaya Manusia pada Perusahaan Jasa Angkutan Taksi: Studi Kasus pada Jember Taksi - Zulkarnain, Deki; Poernomo, Djoko; Wahjuni, Sri (University of Jember, 2016)
Abstract Maintenance is an important process in human resource management in order to ensure the performance of a company. This research applied qualitative research with case study strategy in purpose of determining the maintenance of human resources at Jember Taxi as one of taxi transportation service companies in Jember. Data were collected by using in-depth interviews supported by a variety of archives and documentation and triangulation techniques. Data were analyzed by using Interactive Data Model Analysis. The results showed that the maintenance of human resources in Jember Taxis was not managed effectively in terms of aspects of planning, program implementation method, quality control and evaluation. It was indicated by data on turnover of human resources, so that the growth of company income declined throughout 2015. The importance of maintenance in boosting the company's performance requires Jember Taxi to improve the implementation of maintenance that has been running so far.